The fourth wave in chronic kidney disease (CKD) classification: taking into account the aging kidney (2023)
CKD affects more than 10% of the population worldwide, is strongly associated with accelerated cardiovascular morbimortality, and its prevalence is exponentially higher among older individuals, although this prevalence is just based on estimated GFR (eGFR) and albuminuria [1]. The first CKD classification (2002) was proposed by the KDOQI group; it divided CKD into five categories based on eGFR. This classification was subsequently endorsed by the KDIGO organization. The second CKD classification (2008) subdivided stage 3 into stages 3a and 3b (45–59 and 30–44 ml/ min/1.73 m2, respectively), and incorporated the presence or absence of albuminuria [2]. The third and currently used KDIGO CKD classification (2012) added the albuminuria level: normal (A1), moderate (A2), and severe (A3) [3]. The positive impact that implementation of the current classification has had is not debatable, however it does not take into consideration the age of the patient. Experts in nephrogeriatrics have long suggested that eGFR declines as we age.